Prevalencia de Leptospira spp en equinos de la vereda Guatiguara del municipio de Piedecuesta Santander (2013)
This investigation was carried out in equine, in Guatiguara rural settlement, Piedecuesta municipality of Santander. The aim was to determine the prevalence of Leptospira spp, collecting 42 samples processed by the Colombian Agricultural Institute, using the Microagglutination test (MAT) identifying the following serovar of Leptospira spp: hardjo prajitno, hardjo bovis, pomona, canicola, icterohaemorrhagiae, grippotyphosa, bratislava, copenhageni, ballum, tarassovi, autumnali. The blood serums that presented agglutination equal or bigger than the dilution of 1:100 were considered positives; of 42 blood serum samplings, 28 were positive for one or more serovar analyzed, which represents a prevalence of 66,7% for the population sampled. A total of 11 males and 31 females sampled, 9 (81,8%) and 19 (61,3%) respectively, resulted positive and the prevalence for the different serovars were the following: L. bratislava 53,3% (IC95%:42,4 - 64,2), L. hardjo bovis 28,5% (IC95%:21,8 - 35,3), L. icterohaemorraghiae 26,3% (IC95%:18,2 - 34,4), L. hardjo prajitno 5,1% (IC95%:1,1 - 9,1), L. grippotyphosa 2,8% (IC95%:0,2 - 5,4) y L. pomona 2,6% (IC95%:0,7 - 4,5). The serovar who presented the major prevalence was L. bratislava 53,3%, pointing out that the equine may come to be a guest of maintenance for this serovariety; as the association of seropositivity between age and sex did not find significant statistical difference (a =0.05).